Enhancing Sustainable Development Efficiency Through a Single Smart City Platform: A Cost-Benefit Policy Perspective from Indonesia - Amnesti, Sheila Kusuma Wardani; Adityo, Rayno Dwi; Zulaichah, Siti; Hariz, Hajar Salamah Salsabila; AllahRakha, Naeem (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2025)
The issue of